Prarancangan Pabrik Dibutyl Phthalate dari Phthalic Anhydride dan n-Butanol Kapasitas 20.000 Ton/Tahun - Hidayati, Nur; , Dr. Ir. H. Ahmad M. Fuadi, M.T; , Kusmiyati, S.T, M.T, Ph.D (2015)
Plasticizer is one of the supporting materials for the plastics industry, in particular that of PVC (polyvinyl chloride), which serves forming properties of elasticity or plasticity so that items of plastic supple, malleable and not easily broken. Dibutyl phthalate is one kind of plasticizer used in Indonesia. Taking into account the projected consumption needs of dibutyl phthalate, the capacity of existing production capacity and minimum or maximum then preliminary design of dibutyl phthalate plant with raw materials phthalic anhydride and n-butanol is planned to stand in the industrial area Gresik, East Java, with a land area of 21 370 m2 and a production capacity of 20,000 tons / year in 2020. Manufacture of dibutyl phthalate made by the process of esterification with sulfuric acid catalyst in the non-adiabatic isothermal stirred flow reactor. The reaction takes place in the liquid phase is irreversible and exothermic. At a temperature of 140oC and a pressure of 2 atm. Phthalic anhydride plant needs to have as many as 1601.710 kg / h and n-butanol as 1798.153 kg / hr. Products such as dibutyl phthalate 2525.268 kg / hr. Utilities supporting the process include the provision of water by 5499.3097 kg / h obtained from the Brantas river water, steam demand as much 3753.6383 kg / hour, amounting to 82.69 kW demand for electricity with diesel fuel and compressed air is needed for pneumatic control device. Plant is planned to operate for 330 days per year and employs 186 people, a fixed capital of Rp 357,141,384,142.55 per year. Working capital of Rp 117,228,095,838.89 per year. After-tax profits reached Rp 80,252,914,055.63 year. Percent return on investment (ROI) before tax of 32.10% and after tax of 22.47%. Pay out time (POT) before tax of 2.38 years and 3.08 years after tax. Break even point (BEP) of 44.9%, shut down point (SDP) amounted to 22.73%, IRR based on discounted cash flow (DCF) of 42.0%. Based on the consideration that the ROI, POT, BEP, SDP and IRR calculations for medium-risk plant meets the standard of dibutyl phthalate plant is feasible to set up. Keyword: dibutyl phthalate, esterification, RATB